Coastal Reclamation Policy In Indonesia From The Perspective Of Sustainable Development: Between Investment Interests And Coastal Ecosystem Protection - Nathania Satriawan; Yuni Ristanti (Civiliza Publishing, 2026)
Coastal reclamation is a development policy intended to support economic growth, urban expansion, and investment. However, its implementation frequently causes environmental degradation, spatial conflicts, and social impacts on coastal communities, raising concerns regarding its consistency with sustainable development principles. This study aims to analyse Indonesia’s coastal reclamation policy from the perspective of sustainable development by examining the balance between investment interests and the protection of coastal ecosystems. The research employs a normative legal method using statute and conceptual approaches, supported by qualitative analysis of legislation, scholarly literature, and relevant legal documents. The findings indicate that Indonesia’s regulatory framework has formally incorporated sustainable development principles through provisions on environmental protection, licensing, and coastal management. Nevertheless, implementation remains constrained by the predominance of economic interests, weak environmental compliance monitoring, inadequate regulatory harmonisation, and limited public participation in decision-making. These challenges hinder the achievement of an appropriate balance between economic development, ecological sustainability, and the protection of coastal communities’ rights. The study concludes that coastal reclamation policies require reform by strengthening environmental oversight, improving regulatory coherence, and ensuring meaningful public participation alongside the application of the precautionary principle. Such measures are essential to align reclamation practices with sustainable development objectives and to promote environmentally sound and socially equitable coastal development.